Activation of Hageman Factor by α-Adrenergic Stimulation - McKay, D. G; Latour, J.-G; Parrish, Mary H. (Thrombosis and Haemostasis, 1970)
The infusion of epinephrine in high doses produces disseminated intravascular coagulation by activation of Hageman factor. The effect is blocked by phenoxybenz-amine and is therefore due to stimulation of α-adrenergic receptor sites.